Allelopathy of Pearl Millet as Influenced by Vegetative and Reproductive Stage of Crop Growth - Saxena, Anurag; Singh, D v; Joshi, N L (Annals of Arid Zone, 2016)
The root and shoot aqueous extracts from vegetative and reproductive stages of pearl millet w. MH 179 were assayed at germination of 20. 40, 60 AND 80 g L-1 (fresh weight basis) for their effects on seed germination and early seedling grouth of pearl millet. Rate of germination declined with increase in concentralion of hoth root a ' shoot extracts while ultimate germination. mot and shoot length were maximum at 20 L-1 mnrrntration and decreased with further increase in concentrations with extracts vegerati~s tage. These parameters were inversely related with the extracts mneentrali nf reproductive stage and over minimum at the highest concentration.The highest mnrentralion iayed resulted in 17.7 and 29.4% decline over control in germination with mot and shmt rarts of vegetative stage. '[he corresponding decline caused by m n r l s of reproductive ge was 57 and 25.6%. respectively. 'The results of the study suggest that extracts of reproductive stage were more phytotoxie than the extracts of vegetative stage.